URGENSI BERZAKAT MELALUI AMIL DALAM PANDANGAN ILMU EKONOMI ISLAM - WIDI NOPIARDO (Institut Agama Islam Negeri Batusangkar, 2017)
Zakat (Divine Tax) is the only worship in Islam where the person responsible for collecting the Zakat mentioned in the Quran. This person is called amil (collector). Therefore, the legal basis for the amil is obviously stated in the Quran and the Sunnah. Even, the prophet pbuh and the companions have shown how to pay zakat through the amil. There must be no doubts paying zakat through amil. However, some phenomena show that the zakat that is paid directly by the tax payer (muzaki) to those who deserve to have it (mustahik). Those phenomena leave a very serious question: whether the receivers are truly mustahik. This is quite reasonable since most of the muzaki distribute their own zakat to their own relatives while many others in their neighborhood deserve to receive more than the others due to their economic conditions.